P06.03 Child, parent, and clinician selection of patient-reported outcome measures to use in pediatric neuro-oncology outpatient follow-up clinics. (9th September 2021) - Bull, K S; Stubley, S; Freeman, A; Liossi, C; Darlington, A E; Grootenhuis, M A; Hargrave, D; Morris, C; Walker, D A; Kennedy, C R
Abstract: BACKGROUND: Survivors of childhood brain tumours are at risk of poor health-related quality of life (HRQoL). Appropriate and relevant measures can be used to monitor HRQoL so that timely interventions may be made for issues thus identified. We had previously selected patient-reported outcome measures (PROMs) with good psychometric properties that had emerged as well-suited for this use in two systematic reviews. The aim of the present study was to ascertain the views of families regarding the suitability of the selected measures for use in paediatric neuro-oncology follow-up clinics. These views were then used to inform the choice of PROMs for use on the KLIK PROM portal, a website designed to gather HRQoL information from families. MATERIAL AND METHODS: As part of the PROMOTE study, we used a multi-centre, multi-informant, cross-sectional, qualitative methods research design. Using 'think aloud' audio-recorded interviews, children aged 8–17 years diagnosed within the previous five years with a brain tumour, off treatment and receiving outpatient care, and their parents, were shown a total of nine PROMs and asked to express their views on which they preferred. Detailed notes were made of all audio-recordings by two independent researchers. The final choice of PROMs to be included on the KLIK PROM portal was agreed through discussion of the PROMs selected by families with an expert panel of clinicians, researchers, and parent representatives. RESULTS: 16 children and 17 parents participated and of these 2 children and 2 parents did not express a preference. The Pediatric Quality of Life Inventory (PedsQL) Core module was the most popular among the children and parents with 7/14 (50%) of children selecting it as either their 1st or 2nd choice citing that they liked the questions and felt them to be most relevant to them, and 8/15 (53%) of parents citing that it was easy, quick and simple, the wording was easy, and they liked the questions about emotional, social, and school functioning. The least popular questionnaires, with no participants selecting them as first choices, were the Kidscreen-10 and the Health Utilities Index. The latter 2 were selected only as 2nd or lower choices by 1 child and 3 parents respectively. CONCLUSION: The PROMs that were finally selected for the KLIK PROM portal were the parent- and child-report PedsQL-Core measures of HRQoL due to their good psychometric properties, family and clinician preference and perceived relevance to follow-up care, and for clinical utility on the KLIK PROM portal.